2019
DOI: 10.3389/fmicb.2019.01266
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo Efficacy of a Synergistic Combination of Itraconazole and Verapamil Against Aspergillus fumigatus

Abstract: The incidence of aspergillosis continues to rise sharply, while the progress made in expanding the antifungal drug arsenal remains extremely slow, indicating an urgent need for new strategies. Previous studies have shown that the calcium signaling pathway, which is evolutionarily conserved in mammals and fungi, is involved in regulating the tolerance of azoles in fungi. In this study, we performed a preliminary screening among various combinations of different clinical calcium channel blockers and different an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…In addition, verapamil enhances the antifungal activity of tunicamycin or fluconazole against C. albicans during biofilm formation and pre-formed biofilms (Yu et al 2013 ). In A. fumigatus , the drug efflux pump was blocked and ergosterol content was decreased following treatment with verapamil and itraconazole simultaneously (Zeng et al 2019 ). Other CCBs, such as diltiazem, nicardipine, and nifedipine, have shown antifungal activity against C. albicans , C. glabrata , Ascomycetous, and Mucoralean fungi, either alone or in combination with antifungals (Bulatova and Darwish 2008 ; Homa et al 2017 ; Alnajjar et al 2018 ).…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%
“…In addition, verapamil enhances the antifungal activity of tunicamycin or fluconazole against C. albicans during biofilm formation and pre-formed biofilms (Yu et al 2013 ). In A. fumigatus , the drug efflux pump was blocked and ergosterol content was decreased following treatment with verapamil and itraconazole simultaneously (Zeng et al 2019 ). Other CCBs, such as diltiazem, nicardipine, and nifedipine, have shown antifungal activity against C. albicans , C. glabrata , Ascomycetous, and Mucoralean fungi, either alone or in combination with antifungals (Bulatova and Darwish 2008 ; Homa et al 2017 ; Alnajjar et al 2018 ).…”
Section: Antiarrhythmic Drugsmentioning
confidence: 99%
“…For example, Lafleur and colleagues (2013) showed that a suboptimal dose of fluconazole (0.005%) can be potentiated by 2-adamantanamine (AC17) in an in vivo guinea pig model of cutaneous candidiasis (68). Another study demonstrated a synergistic effect of verapamil and a suboptimal itraconazole dose in vivo, resulting in a reduced fungal lung burden in mice infected by Aspergillus fumigatus (69). To test the MCZ-DB combination in vivo, a formulation containing 1% MCZ nitrate and 0.144% DB was used.…”
Section: Combination Treatment With Imidazoles and Db Is Fungicidal Against C Albicans Biofilmsmentioning
confidence: 99%
“…Previous reports have indicated that ergosterol inhibitors can interact positively with antagonists of calcium channels against fungal organisms (26,27) and trypanosomatids (12)(13)(14). Here, we investigate if amlodipine, a CCB used clinically as an antihypertensive agent, could increase the anti-T. cruzi activity of ravuconazole in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Amlodipine is among the best-studied agents that reverse resistance of Plasmodium to antimalarial agents (28), and accumulating evidence suggests that some CCBs can enhance the antifungal activity of azole derivatives by interfering with efflux pumps and/or influencing calcium signaling pathways (26,27). The drug has also exhibited broad-spectrum antibacterial activities and in vitro synergistic antimicrobial effects on multidrug-resistant microorganisms (29).…”
Section: Discussionmentioning
confidence: 99%